Energy crops for sustainable phytoremediation – Fuel characterization. (February 2019) - Werle, Sebastian; Tran, Khanh-Quang; Magdziarz, Aneta; Sobek, Szymon; Pogrzeba, Marta; Løvås, Terese
Abstract: Two energy crops Miscanthus x giganteus and Sida hermaphrodita were used for a phytoremediation study on two different sites of soil contaminated with heavy metals in Poland and Germany. The energy crops were harvested and characterized with regards to fuel properties and thermal decomposition behaviour. Site influences on the data of proximate and ultimate analyses have been observed. Differences in the thermal decomposition are caused by the differences in pH value and heavy metal content of the soils.